2018
DOI: 10.3390/nu10020241
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Maternal Nutrition during Pregnancy and Offspring Kidney Structure and Function in Humans: A Systematic Review

Abstract: The intrauterine environment is critical for fetal growth and organ development. Evidence from animal models indicates that the developing kidney is vulnerable to suboptimal maternal nutrition and changes in health status. However, evidence from human studies are yet to be synthesised. Therefore, the aim of the current study was to systematically review current research on the relationship between maternal nutrition during pregnancy and offspring kidney structure and function in humans. A search of five databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 61 publications
2
24
0
3
Order By: Relevance
“…Newborn babies of the mothers with VAD had significantly lower mean retinol levels and the dimensions of both kidneys were smaller than those of the newborns of mothers with vitamin A sufficiency [63]. A recent systematic review found an association between vitamin A deficiency in pregnancy and a negative effect on kidney function and kidney structure in the child [107].…”
Section: Vitamin a And Pregnancy: Importance And Effects Of Deficimentioning
confidence: 99%
“…Newborn babies of the mothers with VAD had significantly lower mean retinol levels and the dimensions of both kidneys were smaller than those of the newborns of mothers with vitamin A sufficiency [63]. A recent systematic review found an association between vitamin A deficiency in pregnancy and a negative effect on kidney function and kidney structure in the child [107].…”
Section: Vitamin a And Pregnancy: Importance And Effects Of Deficimentioning
confidence: 99%
“…A similar nding was also reported from another Chinese study which indicates famine exposure was linked to a greater risk (OR 1.54, 95% CI 1.04, 2.28) of higher protein urea among women rural participants [14]. Corroborating the above ndings, a recent systematic review reported unfavorable changes with kidney structure and function, measured by kidney volume, proteinuria, eGFR and mean creatinine clearance in the offspring of mothers with folate, vitamin A, and total energy de ciencies during pregnancy [29].…”
Section: Discussionmentioning
confidence: 89%
“…A systematic review analyzed the relation between human nutrition during pregnancy and kidney structure and function in offspring. Deficiencies in VA, along with other folate and total energy, were associated with negative outcomes on kidney structure and function using outcomes of kidney volume, proteinuria, glomerular filtration rate, and creatinine clearance ( 146 ). Mouse model investigations of embryological development have provided evidence that maternal VAD can inhibit normal fetal pancreatic ( 147 ) and anorectal ( 148 ) development in utero.…”
Section: Resultsmentioning
confidence: 99%